Perancangan Interior Musem Wayang Potehi di Surabaya - Grace Mulyono, Faradila Chandra (Intra, 2014)
The potehi puppet was a culture from Chinese be in the form of handâs doll which played with colonial story. In the period of reformation, the potehi puppet had no permition from President wheresoever to all Chinese culture canât show in public. Nowadays Chinese culture can show in public again. But many people had no interest for this culture because they assuming that thing so boring. Surabaya is a East Javaâs capital where the potehi puppet came for the first time through marketâs route ago so this place will be so compatible if there is a museum of potehi puppet. Hopefully, with this design planning people will have a place to give more acknowledges from one of Chinese culture where they were minority in Indonesia and so ever got discrimination in new ordeâs period, knowing Indonesia is âBhineka Tunggal Ikaâ.